Reflection of Plane Waves in a Transversely Isotropic Rotating Microstretch Elastic Half-Space - Gupta, Princy; Sikka, Jitander Singh (Communications in Mathematics and Applications, 2023)
. In this paper, the impact of rotation on the propagation of plane waves for various rotation parameter values has been studied. For this purpose, a model has been developed which is assumed to rotate with uniform angular velocity. A transversely isotropic solid medium with microstretch elastic properties has linear governing equations that are focused in the x-z plane. For the incident Coupled Longitudinal Displacement (CLD) wave, four reflected coupled plane waves exists in the same medium. A half-space surface with no stresses of a material is thought to exist where the CLD wave reflects. On the stress-free surface of the half-space, the appropriate potentials for the incident and reflected waves satisfy the necessary boundary conditions, and relationships in the amplitude ratios of reflected waves are obtained. Graphs of plane wave speeds and amplitude ratios versus propagation angle are shown for various values of the rotation parameter